Diet items of manatee Trichechus manatus manatus in three priority sites for the species in Mexico and Belize - Flores-Cascante, Lavinia (2013)
Manatees (Trichechus manatus manatus) are herbivorous mammals with opportunistic habits that feed on approximately 60 species of plants. The focus of this paper was to identify diet elements of the manatee by fecal analysis in two sites in Mexico (Jonuta, Tabasco and Bahía de la Ascensión, Quintana Roo) and one site in Belize (Southern Lagoon). Samples were obtained from wild manatees and captive manatees temporarily captured for health assessment and sampling during 2004-2006. A total of 24 samples were analyzed. Diet components were assessed by microhistological analysis of feces. Items were separated and compared with bibliography and histological collections. Samples were also analyzed to detect invertebrates. Vegetal species found included Thalassia testudinum, Rhizophora mangle, Halodule wrightii, Ruppia sp. and Panicum sp., the latter confirmed for the first time for Mexico. No evidence of invertebrates was found in the samples. Relative importance of vegetal species consumed by manatees coincides with the findings reported for other areas in the Americas. Further systematic sampling efforts are needed in areas where manatee diet items are unknown.